Stochastic fractal based multiobjective fruit fly optimization - Zuo, Cili; Wu, Lianghong; Zeng, Zhao-Fu; Wei, Hua-Liang (Zielona Góra: Uniwersytet Zielonogórski)
The fruit fly optimization algorithm (FOA) is a global optimization algorithm inspired by the foraging behavior of a fruit fly swarm. In this study, a novel stochastic fractal model based fruit fly optimization algorithm is proposed for multiobjective optimization. A food source generating method based on a stochastic fractal with an adaptive parameter updating strategy is introduced to improve the convergence performance of the fruit fly optimization algorithm.
Keywords: multiobjective optimization; fruit fly optimization algorithm; stochastic fractal